Edytorskie plany administracji oświatowej Królestwa Polskiego w latach 1862-1864 - Kwiatkowska, Magdalena (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The change of the policy after the death of tsar Nicholas I and the progress of events in Królestwo Polskie in the period previous to January uprising (1863) made it possible for higher education institutions closed down after November uprising (1830) to be restored. Among them there were the university (Szkoła Główna Warszawska, 1862-1869) which became one of the symbols of the Polish culture in the second part of the 19th century.After the thirty year period when the activity of the Polish academic institutions was interrupted, the lack of scientific publications – mainly manuals and basic works of the European science was noticeable. Szkoła Główna, founded in extraordinary political circumstances, did not have adequate financial means to finance publications and its statutes did not include publishing activity. It could only act as an initiator of editing enterprise in regard to ready to publish texts and works in statu nascendi.There have been few records handed down both in official government documents and in private hands, inherited from the participants of the events. There were plans to publish two natural science manuals and the rector of Szkoła Główna suggested publishing Bibliografia Polska XIX stulecia by Karol Estreicher.The financial resources to cover the costs of the publishing were probably provided by the special fund (approx. 23.000 roubles)established by the polish education administration re-created in march 1861. The following people were in charge of the institution in succession: Aleksander Wielopolski until September 1861, Romuald Hube until June 1862, Kazimierz Krzywicki until September 1863 when it went back again into the hands of Russian officers appointed by the Russian authorities. Both, the plan to publish translations of the outstanding foreign works, which were to be used in secondary schools and universities as well as the costly edition of the watercolours which was the outcome of the official Polish monument listing in Królestwo Polskie (1844-1855) were the ideas of the contemporary environment.Due to political reasons and the short activity of the Polish department of education, the editorial plans of Szkoła Główna were never brought into being.